Interrelation between extracellular vesicles miRNAs with chronic lung diseases. Issue 11 (5th September 2022) - Dhar, Rajib; Mukherjee, Sayantanee; Mukerjee, Nobendu; Mukherjee, Dattatreya; Devi, Arikketh; Ashraf, Ghulam Md; Alserihi, Raed F.; Tayeb, Hossam H.; Hashem, Anwar M.; Alexiou, Athanasios; Thorate, Nanasaheb
Abstract: Extracellular vehicles (EVs) are nanoscale lipid bilayer vesicles that carry biologically active biomolecule cargos like proteins, lipids, and nucleic acids (DNA, RNA) outside of the cell. Blood (serum/plasma), urine, and bronchoalveolar lavage fluid are all examples of biofluids from which they may be collected. EVs play a vital role in intracellular communication. The molecular signature of EVs largely depends on the parental cell's status. EVs are classified into two groups, (1) exosomes (originated by endogenous route) and (2) microvesicles (originated from the plasma membrane, also known as ectosomes). The quantity and types of EV cargo vary during normal conditions compared to pathological conditions (chronic inflammatory lung diseases or lung cancer). Consequently, EVs contain novel biomarkers that differ based on the cell type of origin and during lung diseases. Small RNAs (e.g., microRNAs) are transported by EVs, which is one of the most rapidly evolving research areas in the field of EVs biology. EV‐mediated cargos transport small RNAs that can result in reprograming the target/recipient cells. Multiple chronic inflammatory lung illnesses, such as chronic obstructive pulmonary disease, asthma, pulmonary hypertension, pulmonary fibrosis, cystic fibrosis, acute lung injury, and lung cancer, have been demonstrated to be regulated by EV. In this review, we will consolidate the current knowledge and literature on the novel role of EVs and their small RNAs concerning chronic lung diseases (CLDs). Additionally, we will also provide better insight into the clinical and translational impact of mesenchymal stem cells‐derived EVs as novel therapeutic agents in treating CLDs.